School efforts to promote parental involvement: the contributions of school leaders and teachers. Issue 1 (2nd January 2022) - Yulianti, Kartika; Denessen, Eddie; Droop, Mienke; Veerman, Gert-Jan
ABSTRACT: School leaders and teachers are two important agents within the school organisation to promote parental involvement. The aim of the study was to investigate how school leaders and teachers foster parents' involvement in their children's education. It was hypothesised that both transformational school leadership for the support of parental involvement and inviting behaviour from the part of teachers encourage parents to become more strongly involved with their child's education. Surveys were administered to 2, 151 parents and 90 teachers of 18 elementary schools spread across Java, Indonesia and analysed using multilevel regression analyses. Results showed that transformational leadership did not have significant direct effects on parental involvement. Significant effects were found of teacher invitations on parental involvement. In particular, teacher invitations contributed to school-based parental involvement, such as recruiting parents as volunteers and involvement in decision-making at school.